Educação ambiental e ensino por investigação: contribuições para ressignificação das representações sociais de meio ambiente de estudantes do Ensino Médio - Silva, Harrysson França Dias da (2022)
Social representations are formed from common sense, the so-called consensual universe, and it is through this phenomenon that subjects interact and interpret the surrounding environment. Therefore, the present study aims to contribute to the resignification of the social representations (SR) of the environment of high school students, and whether investigative classes in non-formal teaching environments (natural environments) can contribute to the transversalization of Environmental Education (AND THE). The research took place in a high school, located in the municipality of Vitória/ES, close to the Fonte Grande State Park, and a portion of mangrove still preserved, which is contained in the former FAESA (Integrated Colleges of São Pedro) land. In the northwest bay of Vitória. The target audience was submitted to free evocation techniques and the socio-environmental thematic form - FTS, in addition to a questionnaire to survey social representations. The data were analyzed and treated through semantic grouping, calculation of the average order of evocations (OME), and the frequency of the categories (F) to structure the Vergès diagram, in addition to plotting graphs from the FTS and using categories of social representations of the environment. The investigative classes in natural environments were planned through investigative didactic sequences. Thus, it was possible to evidence that the triangulation of the data of these three instruments becomes important to investigate the SR of the environment of a certain group. Furthermore, changes in these SRs occur slowly due to the difficulty in breaking the common sense that forms them (the consensual universe), as well as the issue of contribution to the transversalization of EE, and that for the occurrence of a resignification it is necessary to know these RS before an intervention, in addition to the time and effort of the teacher. In a way that promotes the formation of critical subjects who understand the relationship between individuals and the environment, understanding its importance for society.